2009
DOI: 10.3340/jkns.2009.45.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Size and Location of Ruptured Intracranial Aneurysms

Abstract: Objective : The aim of study was to review our patient population to determine whether there is a critical aneurysm size at which the incidence of rupture increases and whether there is a correlation between aneurysm size and location. Methods : We reviewed charts and radiological findings (computed tomography (CT) scans, angiograms, CT angiography, magnetic resonance angiography) for all patients operated on for intracranial aneurysms in our hospital between September 2002 and May 2004. Of the 336 aneurysms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 39 publications
6
41
2
1
Order By: Relevance
“…A Korean study also found the average size of aneurysm 6.15±1.3. Average Size of aneurysm found in other study was 7.20±4.30 35 , 5.59±2.79 36 . The size of ACom aneurysm was 6.12±2.7, PCom aneurysm was 6.5±2.4 and MCA aneurysm was 7.79±.71.…”
Section: Discussionmentioning
confidence: 85%
“…A Korean study also found the average size of aneurysm 6.15±1.3. Average Size of aneurysm found in other study was 7.20±4.30 35 , 5.59±2.79 36 . The size of ACom aneurysm was 6.12±2.7, PCom aneurysm was 6.5±2.4 and MCA aneurysm was 7.79±.71.…”
Section: Discussionmentioning
confidence: 85%
“…For both the anterior and the posterior circulation 1 mm images with 0.6 mm overlap were reconstructed with a FOV of 100 mm. (6) where S Auto represents the automated segmentation and S Man represents manual segmentation.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Multiple factors can have an effect on the rupture risk of the aneurysm such as environmental factors (e.g. smoking, hypertension and alcohol consumption) [1], size [3], [4], [5], [6], [7] and shape [8], [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Paraophthalmische Aneurysmen repräsentieren ungefähr 0,5 % aller rupturierten Aneurysmen [4,5]. Wie andere intradurale Aneurysmen stellen sie einen Risikofaktor für das Auftreten einer Subarachnoidalblutung dar, auch wenn einzelne Studien die Vermutung nahelegen, dass das Blutungsrisiko bei paraophthalDie Ergebnisse wurden in einem Vortrag auf dem DOG-Kongress 2016 in Berlin präsentiert.…”
Section: Management Paraophthalmischer Aneurysmen üBersicht Der Endovunclassified